Ant Colony Optimization Algorithm for Design of Distribution System with Practical Application - حسن, فارس طاهر; سعيد, اماني صديق (Journal of Economics and Administrative Sciences, 2015)
The Ant System Algorithm (ASA) is a member of the ant colony algorithms family in swarm intelligence methods (part of the Artificial Intelligence field), which is based on the behavior of ants seeking a path and a source of food in their colonies. The aim of This algorithm is to search for an optimal solution for Combinational Optimization Problems (COP) for which is extremely difficult to find solution using the classical methods like linear and non-linear programming methods.  The Ant System Algorithm was used in the management of water resources field in Iraq, specifically for Haditha dam which is one of the most important dams in Iraq. The target is to find out an efficient management system for the dam that ensures optimal monthly water storage and drainage volumes.  The water study duration was for five years starting from first of October 2007 until September 30th, 2012. The data for these five years represents time series for monthly volumes of water demand, drainage, evaporation and storage. A new management system was proposed for Haditha dam that ensures a monthly storage volumes within the designed storage capacity of the reservoir and ensures no shortage with water availability that causes the usage of the dam turbine units. These results are optimal generation of hydroelectric energy and rationalization of electricity. The algorithm was developed and executed using Matlab software.